PENERAPAN MODEL PEMBELAJARAN PBL BERBANTUAN WORDWALL UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V UPT SPF SDN LABUANG BAJI 1 - Nurmuthahira Syam; Ardandi; Wawan Aprilianto; Rezki Ramdani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The problem in this research is the low mathematics learning outcomes of students in class V.B UPT SPF SDN Labuang Baji 1, so with this problem this research was carried out with the aim of improving mathematics learning outcomes by using the PBL (Problem Based Learning) learning model assisted by wordwall in the VB UPT SPF class. SDN Labuang Baji 1. Based on the results of initial assessment observations that have been carried out, there are student learning outcomes below the KKM, namely 70. This is motivated by students' difficulties in understanding mathematics learning so that students feel they are not interested in learning mathematics because they think mathematics is a difficult learning difficult and boring. The type of research used is Classroom Action Research (PTK) or Classroom Action Research. The data used is quantitative and qualitative data. The data collection techniques used are observation, tests and documentation. The research instruments in this study were tests and observation sheets. The results of this research show that there was a presentation of student learning outcomes in pre-cycle 64.28%, cycle I 71.42%, and cycle II 85.71%. So, based on the research results, it can be concluded that the application of the PBL learning model assisted by wordwall can improve the mathematics learning outcomes of students in class VB UPT SPF SDN Labuang Baji 1